Allergens in celery and zucchini - Vieths, S.; Lüttkopf, D.; Reindl, J.; Anliker, M. D.; Wüthrich, B.; Ballmer‐Weber, B, K. (Allergy (Copenhagen), 2002)
The aim of this study was to confirm allergy to celery tuber and to zucchini, for the first time, by DBPCFC, and to identify the allergens recognized by IgE from DBPCFC‐positive patients. Therefore, raw vegetables were hidden in a broccoli drink, and a DBPCFC‐procedure was developed that consisted of a spit and swallow protocol, making sure that the procedure was safe for the patients and that reactions strictly localized to the oral cavity as well as systemic reactions could be reproduced by DBPCFC. The allergens in celery and zucchini extract were identified by immunoblot inhibition using allergen extracts, recombinant allergens and purified N‐glycans as inhibitors. Celery allergy was confirmed in 69% (22/32) of subjects with a positive case history. Four subjects with a history of allergic reactions to zucchini had a positive DBPCFC to this vegetable. During DBPCFC, systemic reactions were provoked in 50% (11/22) of the patients to celery, and in 3/4 of the zucchini‐allergic patients. The Bet v 1‐related major celery allergen was detected by IgE of 59% (13/22) of the patients. Cross‐reactive carbohydrate epitopes (CCD) bound IgE of 55% (12/22) of the celery‐allergic patients and in 2/4 of the subjects with zucchini allergy. Profilin was a food allergen in celery in 23% (5/22) and in zucchini in 2/4 of the cases. A zucchini‐specific allergen was detected by IgE from one patient. We conclude that ubiquitous cross‐reactive structures are important in allergy to both, celery and zucchini, and that a specific association to birch pollen allergy exists in allergy to celery (mediated by Api g 1), but not in zucchini allergy.